Marco regulatório da pós-graduação stricto sensu na UFPB: balizas jurídicas ao desenvolvimento institucional - Oliveira, Fábio Abrantes de (2017)
The main objective of this research is to contribute to the development of the management of the stricto sensu postgraduate class at the Federal University of Paraíba, through a survey of the legislation that regulates the sector within the UFPB. The importance of the subject is due to the fact that the stricto sensu graduate is seen as a central lever for the scientific and technological development of Brazil, needing to follow, discuss, understand and interfere in the national, regional and local realities. The University thus gains great importance for overcoming the present challenges, since it has multidisciplinary conditions to understand social and environmental phenomena from all angles and to point out the possible solutions. Little is known that the implementation of existing postgraduate management models and / or the transition to new models are engendered in legal frameworks originated in administrative law and may become possible obstacles to the elaboration or implementation of strategies that allow the modernization of the management, control of activities and evaluation of the results of the administration of that area in universities. In order to do so, a theoretical framework will be presented supporting the concepts of development as a historical phenomenon, planning as an essential function of the administration of a Federal Educational Institution, and also the legislation that regulates the stricto sensu postgraduate in the scope of UFPB, confronting it with national legislation, through descriptive research, using the inductive method of approach. Because it is a research whose nature is applied, it is one of its purposes the creation of a compendium on the legislation of the post-graduation stricto sensu in the UFPB, from 2002 to 2015, aiming to contribute with the Administration and the various actors involved with the various areas in the Institution.